2018
DOI: 10.1007/s10811-018-1604-1
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of genetic structure of Porphyra umbilicalis Kützing in the Gulf of Maine using SNP markers from RNA-Seq

Abstract: The red alga Porphyra umbilicalis Kützing has a broad distribution within the North Atlantic. In the Northeast Atlantic, P. umbilicalis is dioecious and reproduces both sexually and asexually, while in the Northwest Atlantic, only asexual reproduction has been observed. In this study, transcriptomes were mined to identify putative single nucleotide polymorphisms (SNP) markers. A computational pipeline was developed that accounts for the specific characteristics of transcriptome dataset, filtered against the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Blouin and Brawley (2012) concluded that there was evidence for apomixis based on the resampling of genotypes using amplified fragment length polymorphisms (AFLPs). Eriksen et al (2016) and Cao et al (2018) also interpreted their results as evidence for apomixis, but both studies were based on a handful of markers only. The former used three microsatellite loci derived from expressed sequence tags (ESTs) and, therefore, the loci were unlikely to be neutral.…”
Section: Bangiophyceae*mentioning
confidence: 99%
“…Blouin and Brawley (2012) concluded that there was evidence for apomixis based on the resampling of genotypes using amplified fragment length polymorphisms (AFLPs). Eriksen et al (2016) and Cao et al (2018) also interpreted their results as evidence for apomixis, but both studies were based on a handful of markers only. The former used three microsatellite loci derived from expressed sequence tags (ESTs) and, therefore, the loci were unlikely to be neutral.…”
Section: Bangiophyceae*mentioning
confidence: 99%
“…Together with its importance in aquaculture, this has led to strain characterization and breeding programs [37,38]. Porphyra has been seen as model organism for red seaweeds and genetic research has been undertaken, including genomic sequencing [16,[39][40][41][42][43][44].…”
Section: Porphyra Constituentsmentioning
confidence: 99%
“…Proximate ash content for Porphyra.Citation: van Groenigen J, Derksen GCH, Timmermans KR (2022) Review of Presence, Induction and Isolation of Major Cellular Constituents From Porphyra Sensu Lato (Rhodophyceae), Including Mycosporine-Like Amino Acids (MAA's). J Mar Biol Aquaculture Res 4(1):[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that intensive inbreeding and selection during the domestication process may reduce the genetic diversity (Voisin et al, 2005;Doebley et al, 2006;Veasey et al, 2008;Provan et al, 2013;Cao et al, 2019). Some previous reports have assessed the genetic diversity and population structure of S. japonica populations in China and indicated that intensive selection and inbreeding for multiple generations are likely to have an effect on the genetic diversity of cultivated S. japonica populations (Wang et al, 2005;Shan et al, 2010;Bi et al, 2011;Liu F. et al, 2012).…”
Section: Introductionmentioning
confidence: 99%